Endothelial dysfunction and oxidative stress in children with sleep disordered breathing: Role of NADPH oxidase. Issue 1 (May 2015) - Loffredo, Lorenzo; Zicari, Anna Maria; Occasi, Francesca; Perri, Ludovica; Carnevale, Roberto; Angelico, Francesco; Del Ben, Maria; Martino, Francesco; Nocella, Cristina; Savastano, Vincenzo; Cesoni Marcelli, Azzurra; Duse, Marzia; et al.
Abstract Objective Oxidative stress plays a crucial role in impairing endothelial function in sleep disordered breathing (SDB) but the underlying mechanism is still undefined. The objective of this study was to evaluate the interplay between oxidative stress, assessed by serum isoprostanes (8-iso-PGF2α) and soluble NOX2-dp (sNOX2-dp), and endothelial function, assessed by flow-mediated dilation (FMD), in children with SDB and healthy controls (HC). Methods One-hundred forty-four children including 45 with primary snoring (PS), 22 with obstructive sleep apnea (OSA) and 67 HC were recruited in this study; in 15 out of 22 OSA children FMD, serum 8-iso-PGF2α and sNOX2-dp were assessed before and after one month post adeno-tonsillectomy (AT). Results Compared with HC, OSA and PS children had significantly higher sNOX2-dp and serum 8-iso-PGF2α levels and lower FMD; compared with PS, FMD was significantly lower in OSA children. No significant difference for sNOX2-dp and serum 8-iso-PGF2α was observed between OSA and PS children. FMD was inversely correlated with sNOX2-dp levels (p < 0.001) and with serum 8-iso-PGF2α (p < 0.001). In multiple linear regression analysis, sNOX2-dp (p < 0.001) and serum 8-iso-PGF2α (p < 0.001) were the only independent predictive variables associated with FMD. AT significantly decreased sNOX2-dp and serum 8-iso-PGF2α levels (from 38.2 ± 8.8 to 22.4 ± 11.1 pg/ml, p < 0.001, and from 281.4 ± 69.7 to 226.0 ± 66.4 pg/ml, p < 0.001, respectively); conversely, FMD significantly increased after AT in OSA children (from 3.0 ± 1.5 to 8.0 ± 2.8%, p < 0.001). Conclusion This study suggests that NOX2-derived oxidative stress is involved in artery dysfunction in SDB children. Such hypothesis is reinforced by FMD improvement after AT coincidentally with oxidative stress lowering. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02247167.